Effect of some medicinal herbs on natural humoral immunity in turkeys Running title: Effect of herbs on natural in turkeys - Sotirov, Lilyan (Journal of the Hellenic Veterinary Medical Society, 2022)
Infectious diseases cause devastating economic losses in the poultry industry. It is important to boost factors of natural immunity to improve defense against infectious diseases in birds. The experimental groups (105 turkey poults allocated to 7 treatment groups) received basal diet plus 1% dry herbs or 0.01% essential oils supplements obtained from the herbs (Chamomilla; Rosemary; Lavender; Oregano; Thyme; St. John's Wort). Blood serum lysozyme concentrations, the alternative pathway of complement activation (APCA), and betalysin activities were determined. The highest blood lysozyme concentrations were determined among the control group and groups supplemented with dry herbs - rosemary, oregano, and thyme. АPCA activity was the highest in the thyme-supplemented group followed by the non-supplemented one. Betalysin activities were the highest in groups receiving lavender, thyme, and oregano, while the lowest levels were found out in chamomile-supplemented birds. In groups treated with essential oils (EO), blood serum lysozyme concentration was the highest in the group treated with rosemary EO, followed by the control group, while the lowest activity was established in birds that received EO from Saint John’s wort. The highest APCA activity was found in the lavender-treated group, and the lowest – in rosemary-treated turkeys. The highest betalysin activity was found among the groups treated with thyme, oregano, and Saint John’s wort, and the lowest activity was determined in the control group. It could be concluded that studied herbs possess an important immunomodulating potential in turkeys, which could improve their health and consequently, their productive performance.